PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SD NEGERI 1 KOTA LANGSA - Maghfirah, Addina; Theresia, Natasya Delila; Muhrijah, Ulfa; P Wahyuni, Elly; Anshari, Khairil (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to analyze the effectiveness of the Project-Based Learning (PjBL) model in improving early reading skills among first-grade students at SD Negeri 1 Kota Langsa. This research employed a quasi-experimental method. Data were collected through tests and analyzed using ANCOVA. The sample consisted of students from classes 1A and 1B at SD Negeri 1 Kota Langsa. The results showed that before treatment (pretest), the average early reading scores of students in the experimental and control groups were nearly the same, at 55.3 and 54.8, respectively. However, after treatment (posttest), the experimental group’s average score increased significantly to 86.4, while the control group’s score rose modestly to 69.2. A one-way ANOVA test was conducted to determine whether the difference between the two groups was statistically significant. The ANOVA results showed an F-value of 9.87, which exceeded the F-table value (? = 0.05), indicating a significant difference between the groups. The p-value = 0.003 (< 0.05) also led to the rejection of the null hypothesis (H?). Thus, it can be concluded that the PjBL model has a significant and positive effect on improving students’ early reading skills compared to conventional teaching methods.